The quality effect of supervisory leadership in the employee’s performance and engagement: Building empirical evidence from the civil service in Peru - Romero Romero, Jorge Luis (2022)
Descargue el texto completo en el repositorio institucional de la Sungkyunkwan University: http://www.dcollection.net/handler/skku/000000171620